Effect of the Atlantic Multidecadal Variability on the Global Monsoon - Paul‐Arthur Monerie; Jon Robson; Buwen Dong; Dan L. R. Hodson; Nicholas P. Klingaman (Geophysical Research Letters)
Abstract We assess the effect of the Atlantic multidecadal variability (AMV) on the global monsoon using idealized simulations. Warm AMV phases are associated with a significant strengthening of monsoon precipitation over Northern Africa and India, and anomalously weak monsoon precipitation over South America. Changes in monsoon precipitation are mediated by a change in atmospheric dynamics, primarily associated with a shift in the circulation related to both an enhanced interhemispheric thermal contrast and the remote impact of AMV on the Pacific Ocean, through changes in the Walker circulation. In contrast, the thermodynamic changes are less important. Further experiments show that the impact of AMV is largely due to the tropical component of the sea surface temperature anomalies. However, the extratropical Atlantic also plays a role, especially for northern Africa. Finally, we show that the effect of AMV on monsoons is not linearly related to the magnitude of warming.